Climate change and human security the challenge to local governance under rapid coastal urbanisation - Redclift, Michael R.; Manuel-Navarrete, David; Pelling, Mark.; Edward Elgar Publishing (Cheltenham [England] : Edward Elgar Pub., 2011)
The challenge presented by climate change is, by its nature, global. The populations of the Mexican Caribbean, the focus of this book, are faced by everyday decisions not unlike those in the urban North. The difference is that for the people of the Mexican Caribbean evidence of the effects of climate change, including hurricanes, is very familiar to them. This important study documents the choices and risks of people who are powerless to change the economic development model which is itself forcing climate change.
1. Introduction -- 2. The dynamics of coastal urbanization -- 3. Nature and space in the "discovery" of the Mexican Caribbean -- 4. The development of mass tourism in Mexico -- 5. Human security and governance -- 6. Governance as process : the evolution of "power spheres" and climate change -- 7. Lived experiences on the coast : Holbox and Mahahual -- 8. Conclusion.
Includes bibliographical references and index.
Keywords: Urbanization -- Political aspects; Electronic books